1997
DOI: 10.1074/jbc.272.6.3179
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization Regulates the Enzymatic Activity of Escherichia coli Outer Membrane Phospholipase A

Abstract: The outer membrane phospholipase A (OMPLA) of Escherichia coli is present in a dormant state in the cell envelope. The enzyme is activated by various processes, which have in common that they perturb the outer membrane. Kinetic experiments, chemical cross-linking, and analytical ultracentrifugation were carried out with purified, detergent-solubilized OMPLA to understand the underlying mechanism that results in activation. Under conditions in which the enzyme displayed full activity, OMPLA was dimeric. High de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 43 publications
(54 reference statements)
8
106
1
Order By: Relevance
“…Previous work demonstrated that excess of the detergent C 12 SB leads to dissociation of dimeric OMPLA and subsequent loss in apparent initial enzymatic activity [9]. Thus, after preincubation at 20 mM C 12 SB only 10% residual initial activity was retained.…”
Section: Kinetic Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous work demonstrated that excess of the detergent C 12 SB leads to dissociation of dimeric OMPLA and subsequent loss in apparent initial enzymatic activity [9]. Thus, after preincubation at 20 mM C 12 SB only 10% residual initial activity was retained.…”
Section: Kinetic Modelmentioning
confidence: 92%
“…In£uence of assay parameters on lag phases and enzymatic activity Previously, it was shown that the experimental parameters strongly determine OMPLA activity [9]. Our current activity model Eq.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…In vitro, the phospholipase activity is modulated in a calcium dependent manner by reversible dimerisation. Inhibition by hexadecanesulphonyl £uoride stabilises the dimeric form of OMPLA [38]. In vivo, chemical cross-linking studies indicate the presence of the monomeric form of OMPLA in the outer membrane [38].…”
Section: Evidence For Dimersmentioning
confidence: 99%
“…Inhibition by hexadecanesulphonyl £uoride stabilises the dimeric form of OMPLA [38]. In vivo, chemical cross-linking studies indicate the presence of the monomeric form of OMPLA in the outer membrane [38]. Soni¢cation or induction of bacteriocin release protein activates OMPLA which is a process concurring with dimerisation [39].…”
Section: Evidence For Dimersmentioning
confidence: 99%
See 1 more Smart Citation